KELIMPAHAN DAN KEANEKARAGAMAN SEMUT SEBAGAI BIOINDIKATOR DI KAWASAN HUTAN LINDUNG GUNUNG AMBAWANG-PEMANCING KALIMANTAN BARAT - , SIGIT NORMAGIAT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ants are a group of insects that have important role in ecosystem and also can be an indicator species to detect environment changes due to the occurrence of a disturbance. This study aims to determine how the condition of abundance, ant diversity along the environmental factors that influence it, the potential bio-indicators of ants, and ants segregation in area of mount ambawang-pemancing preserved forest (HLGAP). 7 plots placed at land use system consisting of maize, oil palm, rubber, acacia, shrub, secondary forest 1 and secondary forest 2. Three ant-sampling technique used in the transects that pitfall traps, litter shifter, and direct collecting. Shannon and Wiener diversity index is used to describe the ant and vegetation. Correlation and multiple regression is used to see the influence of environmental factors on ant diversity. While the relationship of environmental factors on the distribution of the ant genus determined by ordination methods such as redundancy analysis (RDA) using 4.5 and CanoDraw Canoco software for windows. Research found 21 genera and 32 species of ants in land use systems HLGAP. lowest abundance was found in the palm oil plantation and acacia are highest. Diversity Index ranges at low to moderate levels. Maize area has a low ant diversity (H '= 1.0), and the highest diversity in secondary forest 1 (H' = 2.22). Bioindicator by the presence of invasive species indicated as disturbed areas, while the land in good condition is indicated by the presence some indigenous of predators species. The results of multiple linear regression analysis showed that the moisture is the main variables that affect the diversity of ant and ant genus segregation that occur is 48,9 % influenced by environmental.